2011
DOI: 10.1093/scan/nsr047
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cortical morphology resulting from long-term amygdala damage

Abstract: The amygdala's contribution to emotion, cognition and behavior depends on its interactions with subcortical and cortical regions. Amygdala lesions result in altered functional activity in connected regions, but it is not known whether there might be long-term structural sequelae as well. We hypothesized that developmental bilateral amygdala lesions would be associated with specific gray matter morphometric abnormalities in the ventromedial prefrontal cortex (vmPFC), anterior cingulate cortex (ACC) and the vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Nonetheless, a recent report on 2 human subjects with longterm, early onset amygdalar damage (Boes et al 2012) demonstrated anomalies in cortical thickness, including both increases and decreases, bearing a spatial distribution with striking resemblance to the results reported here (Fig. 7).…”
Section: Cingulate Cortex Hypertrophysupporting
confidence: 87%
“…Nonetheless, a recent report on 2 human subjects with longterm, early onset amygdalar damage (Boes et al 2012) demonstrated anomalies in cortical thickness, including both increases and decreases, bearing a spatial distribution with striking resemblance to the results reported here (Fig. 7).…”
Section: Cingulate Cortex Hypertrophysupporting
confidence: 87%
“…As Williams syndrome has been associated with changes in AMG functioning [85][86][87], it provides important clues for the role of the AMG. One study reported that long-term damage to the entire AMG did lead to morphometric changes in the ventral stream, but not the dorsal stream [88]. On this account, BLA damage reveals the relative independence of these two routes.…”
Section: (D) Ventral and Dorsal Streammentioning
confidence: 99%
“…With the development of more sensitive neuroimaging methods, more subtle changes can now be detected, making the combination of neuroimaging and patient studies particularly fruitful for studying network-level anatomy, functioning, plasticity, and compensation. For instance, morphometric changes in distal cortex following bilateral amygdala lesions have been observed [109], as have structural changes in white matter following damage to the visual cortex (which may account in part for the striking abilities of patients with visual blindsight [110]).…”
Section: Compensation and Recovery: Towards A Network-view Of The Socmentioning
confidence: 99%